Optimisation de la production énergétique des systèmes photovoltaïques - Seif Eddine djebablia; Oussama SAAIDIA (My University, 2025)
This memoir focuses on optimizing photovoltaic systems by tracking the maximum power point under varying irradiance and temperature. It compares traditional methods such as Perturb and Observe and Incremental Conductance with intelligent approaches like neural networks and fuzzy logic. Simulations using MATLAB/Simulink show that intelligent techniques provide better environmental adaptation and improve the stability and efficiency of power output. ----------------------------------------------------------------------------- تتناول هذه المذكرة دراسة طرق تحسين مردودية الأنظمة الكهروضوئية، من خلال تتبع نقطة الاستطاعة القصوى تحت ظروف إشعاع وحرارة متغيرة .تم تحليل كل من الطرق التقليدية كالاضطراب والمراقبة والتوصيل التزايدي، إلى جانب تقنيات ذكية كالشبكات العصبية والمنطق غير الدقيق .أنُجزت المحاكاة باستخدام برنامج ماتلاب/المحاكاة، وتمت مقارنة فعالية هذه الطرق .أظهرت النتائج أن استخدام تقنيات الذكاء الاصطناعي يحقق تكيّفًا أفضل مع الظروف البيئية، مما يحسن استقرار وكفاءة الإنتاج الكهربائي. ----------------------------------------------------------------------------- Ce mémoire étudie l’optimisation des systèmes photovoltaïques par le suivi du point de puissance maximale sous différentes conditions d’ensoleillement et de température. Il compare des méthodes classiques comme Perturb & Observe et la conductance incrémentale, avec des techniques intelligentes telles que les réseaux de neurones et la logique floue. Les simulations, réalisées sous MATLAB/Simulink, montrent que les approches intelligentes assurent une meilleure adaptation environnementale et améliorent la stabilité de la production.
Keywords: Photovoltaic system; Maximum power point; Artificial intelligence; MATLAB; Simulation.; النظام الكهروضوئي، نقطة الاستطاعة القصوى، الذكاء الاصطناعي، ماتلاب، المحاكاة.; Système photovoltaïque; Point de puissance maximale; Intelligence artificielle